Changes in serum adipokines profile and insulin resistance in patients with rheumatoid arthritis treated with anti-TNF-α. (2nd December 2019) - Corrado, Addolorata; Colia, Ripalta; Rotondo, Cinzia; Sanpaolo, Eliana; Cantatore, Francesco Paolo
Abstract: Background: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease characterized by an altered glucose and lipid metabolism. Tumor necrosis factor alpha (TNF- α ) is involved in the pathogenesis of both RA and metabolic syndrome. This study evaluated the effects of anti-TNF- α agents (adalimumab, etanercept, infliximab) on lipid and glucose metabolism in patients with RA. Methods: A total of 33 RA, biological therapy- naive patients were recruited. Changes in Disease Activity, Body Mass Index, resistin, leptin and adiponectin serum levels, lipid profile, atherogenic index, insulin sensitivity index, and insulin resistance index were evaluated at baseline and after anti-TNF- α treatments. Results: Anti-TNF- α treatment was effective in reducing disease activity. An inverse relationship between disease activity and adiponectin levels was found, whereas leptin and resistin levels directly correlated with disease activity. TNF- α therapy significantly reduced leptin, resistin, and increased adiponectin. TNF- α inhibition resulted in a reduction of atherogenic index and insulin resistance index while increased insulin sensitivity index. Conclusion: Anti-TNF- α agents could have a crucial role in modifying the impact of lipid profile and glucose levels dysregulation in RA patients. TNF- α inhibition may be a potential strategy for the prevention of metabolic syndrome and could play a role in the reduction of cardiovascular risk in RA.